Endoscopic Tattoo Practice at a District General Hospital. (13th March 2011) - Gavin, D; Sidwell, A; Scott, M; Dowler, K; Anderson, J; Shepherd, N; Lucarotti, M
Abstract : Introduction: Without placing an endoscopic tattoo it may be difficult to accurately relocate the site of pathology after removal (eg, polypectomy). The National Bowel Cancer Screening Program (BCSP) have published guidelines on tattoo practice for suspected malignant polyps.1 2 We aimed to test the null hypothesis: there is no difference in tattoo practice between BCSP and non-BCSP lower GI endoscopy. Methods: All reports for lower GI endoscopy performed at our unit over a 3 year period were reviewed. All polyps greater than 10 mm in diameter were identified. Lesions identified clinically and reported as a carcinoma were excluded. Colonoscopies were grouped by indication; either BCSP or non-BCSP. Information was gathered on polypectomy practice, tattoo practice, polyp size and the incidence of a histological diagnosis of polyp cancer. Statistical analysis was performed using χ 2 with Yates correction. Results: A total of 11 679 endoscopy reports were reviewed. A polyp >10 mm in diameter was identified n 556 procedures, 145 in the BCSP (21.9%) and 411 in the non-BCSP (3.7%)(p<0.0001). In the BCSP group 116 tattoos were placed (80% of procedures) while in the non-BCSP group 126 tattoos were placed (30.66% of procedures)(p<0.0001). Excluding caecal and rectal lesion did not significantly alter the tattoo results (83.45% BCSP, 36.63% non-BCSP (p<0.0001)). Polyp malignancy was diagnosed in 14 cases in the BCSP group (9.66%) and in 44 cases in the non-BCSP group (10.71%) (p=0.843). 10 of 14 polyp cancers were tattooed (71.42%) in the BCSP group. 14 of 44 polyp cancers in the non-BCSP group were tattooed (31.82%) (p=0.02). Polypectomy was performed in 142 (97.93%) cases in the BCSP group and in 316 (76.89%) cases in the non-BCSP group (p<0.0001). Conclusion: There is a difference in the management of colonic polyps in our unit. Polyps > 10 mm were more likely to be treated at the index endoscopy and the site of the polyp or polypectomy was more likely to be tattooed if the procedure was performed within the BCSP. Current guidelines published by BCSP and JAG for tattooing of colonic polyps are broadly similar with no reference to polyp size. In our hospital BCSP practice seems to be following a separate BSG Polypectomy Guide3, which state that polyps >10 mm should be tattooed, with superior results. This would suggest that BCSP and non-BCSP colonoscopy guidelines should be updated to improve tattoo practice. Competing interests: None.